Spot Welding Error Analysis in Making Rear Brake Arm in Spot Welding Part at PT. XYZ - Magada Nandika Adicakra; Santoso, Deri Teguh (Jurnal Mesin Nusantara, 2024)
As a manufacturing company engaged in the manufacture of automotive parts, it produces components for motorized vehicles, especially for two wheels, with the production of spare parts in the form of arm rear brakes. In the manufacture of these spare parts, it is really necessary to pay attention to all the needs, such as materials which, in other words, really have an influence on the strength of the material. Included in the process that goes through spot welding, it needs to be considered in the stages of the process to be optimal because, if not, it will cause failure of a product so that defective products are obtained at this welding point. Improvement of the production process of this product can be done by identifying control factors and arrangements using the 5 why analysis, fishbone, and pareto methods until the production process is stable and the results obtained are good and according to the expected standards until the needs of all parties are met.